(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2020)
The purpose of the study is to propose a sustainable tourism model for Buenaventura, Colombia. This city is considered Colombia’s main port in the Pacific, and boasts a wealth of biodiversity and nature reserves. This study seeks to address the development shortfall facing sustainable tourism in Buenaventura, which is related to a lack of facilities and deficient road access to tourist sites. Moreover, public policy does not establish guidelines for the development of tourism. In the absence of human capital with specialized training, learning is carried out empirically. A descriptive-exploratory method was used, which enables triangulation in the processing of primary and secondary information. Video-abstract: https://youtu.be/jtj8krcudtQ